Evaluation of mandibular fracture patterns and treatment methods: A single center retrospective study (Annals of Medical Research, 2023)
Aim: Mandible fractures are among the most common bone fractures in the maxillofacial region. Correct and early treatment is important in mandible fractures. The aim of this study is to retrospectively examine and analyze the patterns and treatment methods of mandibular fractures seen in patients admitted with trauma.Materials and Methods: Patients treated for mandible fractures between 2006 and 2021 years were included in this retrospective study. The files and archive records of the patients were scanned retrospectively. Demographic, clinical and radiological data were recorded. The treatment methods of the patients included in the study were evaluated.Results: 176 patients with a total of 246 fractures were included to the study.  Simple fractures were found in 130 patients, green tree fractures in 12 patients, and comminuted fractures in 34 patients. There were 147 un-favorable and 29 favorable fractures in total. Fall was found to be the most common etiologic cause in all gender and age groups (n=55, 31.2%). Angle fracture was observed most frequently in single fracture cases, while condyle fracture was the most common accompanying fracture type in multiple fractures. 88 patients were treated with the open and, 56 with the closed approach, and 32 with both the open and closed approach.Conclusion: Fracture type and etiologic cause are closely related with the type of the fracture. Mandible fractures should be carefully examined and the most appropriate treatment for the type of fracture should be applied as soon as possible.
Keywords: Mandible fractures; Trauma; Treatment